The international timber trade. - Peck, Tim (Woodhead Pub., 2001)
Wood and wood products are essential to large areas of the world economy, yet until now there has been no single definitive reference source to which those new to or requiring a strategic overview of the industry could turn for a comprehensive picture of the market chain from forest to consumer. The international timber trade remedies this, providing a detailed overview of the entire timber and timber products business in an authoritative and accessible style. Written by a leading expert, The international timber trade is essential reading for a wide range of interested groups including manage.